Paradigma Dakwah Syeikh Ibnul Qoyyim Al Jauziyah : Rekonstruksi Pemikiran Dakwah Harokah - Hayatuddin; Abdul Hamid; Sarbini Anim; Badrah Uyuni (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to reconstruct the da’wah paradigm of Ibn al-Qayyim al-Jawziyyah as an epistemological foundation for the renewal of harakah (movement-based) da’wah thought in the contemporary era. The background of this research lies in the epistemological crisis within da’wah movements, which often become trapped in textual normativism or apologetic reactionism, as well as the limited systematic studies on Ibn al-Qayyim’s contribution to an integrative da’wah paradigm. This study employs a qualitative method with a library research approach, referring to his major works such as I‘lām al-Muwaqqi‘īn, Madārij al-Sālikīn, and al-Dā’ wa al-Dawā’, along with reputable academic literature, analyzed using qualitative content analysis with a critical hermeneutic approach. The findings indicate that Ibn al-Qayyim’s da’wah paradigm is integrative and holistic, encompassing spiritual (tazkiyah al-nafs), rational-ijtihadi (fiqh al-wāqi‘ and maqāṣid al-sharī‘ah), and socio-contextual dimensions. Its reconstruction includes strengthening da’wah bil ḥāl, applying dynamic fiqh al-awlawiyyāt, and developing a non-violent yet critical movement theory, making it relevant for digital and plural societies